The Effect Of Leadership Style, Non-Physical Work Environment, Organizational Culture On Employee Performance Through Motivation at The Immigration Office, South Jakarta - Andini Nurwulandari; Mas Tri Irmawanti (Yayasan Riset dan Pengembangan Intelektual, 2023)
In a work organization, leadership plays a crucial role in organizational activities and even the sustainability of the organization itself. The role of leadership is highly strategic as one of the determinants of success in achieving the organization's vision, mission, and operational plans. The performance of each employee is also highly dependent on the leadership capabilities of the management across all levels, as they coordinate all organizational activities and create a conducive work environment climate. Leadership is the process of influencing or setting an example by the leader to their followers in an effort to achieve organizational goals. The purpose of this study was to analyze the influence of leadership style, organizational culture, work environment, employee performance and motivation as an intervening variable at the Immigration Office Class I Special Non TPI, South Jakarta. The research sample was 102 people selected by random sampling method. Data collection uses a questionnaire and Structural Equation Modeling (SEM) is used as an analysis technique. The results of testing the data found that with direct influence, leadership style, work environment and organizational culture were able to influence employee performance. In indirect influence, only motivation is capable of mediating.